2015
DOI: 10.3390/nu7053524
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Micronutrient Intake among Children in Europe

Abstract: Adequate dietary intake of micronutrients is not necessarily achieved even in resource-rich areas of the world wherein overeating is a public health concern. In Europe, population-based data suggests substantial variability in micronutrient intake among children. Two independent surveys of micronutrient consumption among European children were evaluated. Stratified by age, the data regarding micronutrient intake were evaluated in the context of daily requirements, which are typically estimated in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
1
54
0
3
Order By: Relevance
“…Compared with the children in European countries, the prevalence of calcium, iron, selenium and zinc inadequacies were much higher in Chinese children. For example, in children aged 4-10 years in European countries, calcium intakes ranged from 563mg/d in the Polish girls to 1106mg/d in the Danish boys, with only 32% of the girls and 28%of the boys having calcium intakes below the EAR [8,32]. Compared with the children in the U.S., based on NHANES 2007-2010, calcium intakes were much higher than Chinese children, calcium intakes were 975mg/d and 1047mg/d in U.S. children aged 4-8 years and 9-18 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the children in European countries, the prevalence of calcium, iron, selenium and zinc inadequacies were much higher in Chinese children. For example, in children aged 4-10 years in European countries, calcium intakes ranged from 563mg/d in the Polish girls to 1106mg/d in the Danish boys, with only 32% of the girls and 28%of the boys having calcium intakes below the EAR [8,32]. Compared with the children in the U.S., based on NHANES 2007-2010, calcium intakes were much higher than Chinese children, calcium intakes were 975mg/d and 1047mg/d in U.S. children aged 4-8 years and 9-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Low micronutrient intakes may link to long-term health risks [5][6][7]. Recent European studies suggested that substantial numbers of European children might be at risk due to inadequate intake of micronutrients [4,8]. China's dietary changes are enormous [9,10] and the shifts in foods consumed and eating behaviors will continue to accelerate [11].…”
Section: Introductionmentioning
confidence: 99%
“…While other studies already suggest monitoring of the ongoing programs [34], no current data have been considered for SAC Portuguese population, in international studies [6,7,26,27]. The only available data for children in Portugal are those from [35], were 47% of children aged 6-12 years show an inadequate iodine intake, being islands values even lower [36], which according Vanderpump et al [28] is confirming that the proximity of the sea does not prevent iodine deficiency.…”
Section: Portuguese Situationmentioning
confidence: 99%
“…Population-based data suggests substantial variability in micronutrients intake among children in Europe and data highlight common deficiencies for several micronutrients, such as iodine [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Large population surveys, such as the Nutrition Examination Survey and National Health, have suggested that many children and pregnant women may be affected by Vitamin D deficiency at some point during their lifetime [8,9,10,11,12,13]. Change of habits, such as less sunlight exposure, indoor living, dietary choices, and increasing rates of dietary allergy, are likely playing a significant role in the increase of this rate in some segments of the worldwide population according to the most recent evaluation of public health indicators [11,14,15,16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%